Agro economic performance of Bio-slurry on boro rice cultivation in some sites of Moulvibazar district - Shaheb, MR; Nazrul, MI; Khan, ASM MR (Bangladesh Journal of Agricultural Research, 2017)
Soil fertility in Bangladesh is gradually diminishing and this is now becoming a critical issue. Biogas slurry is a renewable energy produced organic fertilizer can be applied for maintaining the fertility of soil. In this study, a two years experiment was conducted in the year 2011 and 2012 at the farmers field of Moulvibazar district under the agroecological zone 20 (AZE-20). The overall objective of the study was to observe the effect of bio-slurry on the agroeconomic performance of boro rice cultivation at on-farm condition. Three fertilizer treatments viz., T1: Soil test based (STB) inorganic fertilizer for high yield goal (HYG), T2: Integrated Plant Nutrient System (IPNS) based inorganic fertilizer + cowdung bio-slurry 5 tha-1 for HYG and T3: Farmers practice as control i.e. average of 20 farmers fertilizer application dose in boro rice were considered during experimentation. Results revealed that bioslurry based boro rice production is more profitable than chemical fertilizer. The highest grain yield (5.06 t ha-1) was recorded from IPNS with 5 t ha-1 cow dung slurry for HYG (T2) while the lowest yield was obtained from farmers practice. However, yield increase due to application of 5 t ha-1 Cowdung slurry slurry with IPNS based inorganic fertilizer was 115 and 124% compared to STB inorganic fertilizer and farmers followed treatment. Gross margin (Tk.65900 ha-1), benefit cost ratio (2.59) and marginal rate of return (451) were also obtained higher in the same treatment. Thus, nutrient package NPKSZn @102-12-25-18-2 kg + cowdung slurry 5 tha-1 might be helpful to get increased yield and improve soil health in AZE-20. Bangladesh J. Agril. Res. 42(2): 363-371, June 2017